Quality of life measures for myasthenia gravis and evaluation of non‐motor symptoms. Issue 1 (4th January 2015) - Jones, Sarah M.; Gwathmey, Kelly G.; Burns, Ted M.
Abstract Health‐related quality of life measures have become an important tool in measuring clinical outcomes. Disease‐specific health‐related quality of life scales, particularly in diseases that might fluctuate, can draw attention to non‐motor symptoms and guide symptom management. The following review provides an overview of quality of life (QOL) with a focus of disease‐specific QOL measures for myasthenia gravis. We also review the current understanding of non‐motor symptoms in myasthenia gravis and suggest that QOL measures might be a useful way of accounting for these symptoms. After reading the review, the reader will have a better understanding of QOL measures and how they can be used for patient care and clinical research.